Analisis Fatwa DSN MUI NO. 10 DSN-MUI/IV/2000 terhadap Implementasi Akad Wakalah dalam Praktik Kurban Online pada E-Commerce Tokopedia - Lina Nugrawati Hatlessy; Udin Saripudin; Akhmad Yusup (UNISBA Press, 2022)
Abstract. Sacrifice (udhiyyah) is a term for livestock, namely in the form of pets that are slaughtered or used as sacrifices on the feast of sacrifice and the days of Tasyriq solely to get closer to Allah SWT. The sacrificial service began to take effect in the second year of hijriyah, just like the two holidays, zakat mal and zakat fitrah. The implementation is determined based on the Qur'an, sunnah, and consensus of scholars. The online sacrificial practice that is carried out at Tokopedia, the implementation mechanism is by ordering through an application, starting from ordering, selecting the desired animal, and finally the payment process. All the processes are carried out online by the person who sacrificed with the institution that organizes the program. The purpose of this study is to find out how the Concept, Practice and Analysis of DSN-MUI Fatwa No. 10/DSN-MUI/VI/2000 on the Implementation of Wakalah Contracts in Online Sacrifice Practices on Tokopedia E-Commerce. This type of qualitative research uses a normative juridical approach, the research data sources are primary and secondary data sources and data collection techniques using observation, literature study, interviews, documentation. The results of this study are that the implementation and practice of online sacrifices carried out on Tokopedia e-commerce are in accordance with what is stated in the DSN-MUI fatwa No. 10/DSN-MUI/VI/2000. Abstrak. Kurban (udhiyyah) adalah sebutan untuk hewan ternak yaitu berupa binatang peliharaan yang disembelih atau dijadikan kurban pada hari raya kurban dan hari-hari Tasyriq semata-mata dilakukan untuk mendekatkan diri kepada Allah SWT. Ibadah kurban mulai diberlakukan pada tahun kedua hijriyah, sama seperti dua hari raya, zakat mal, dan zakat fitrah. Adapun pemberlakuannya ditetapkan berdasarkan Al-Qur’an, sunah, dan ijma’ ulama. Praktik kurban online yang dilaukan di tokopedia mekanisme pelaksanaannya dengan cara pemesanan melaui aplikasi mulai dari pemesanan, pemilihan hewan yang diinginkan, dan yang terahir yaitu proses pembayaran. Semua prosesnya dilakukan secara online oleh orang yang berkurban dengan lembaga yang menyelenggarakan program tersebut. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana Konsep, Praktik dan Analisis Fatwa DSN-MUI No 10/DSN-MUI/VI/2000 Terhadap Implementasi Akad Wakalah Dalam Praktik Kurban Online pada E-Commerce Tokopedia. Jenis penelitaian kualitatif dengan pendekatan yuridis normatif, sumber data penelitian yaitu sumber data primer dan sekunder dan teknik pengumpulan data menggunakan observasi, studi pustaka, wawancara, dokumentasi. Hasil dari penelitian ini yaitu bahwa implementasi dan praktik kurban online yang dilakukan pada e-commerce Tokopedia sudah sesuai dengan apa yang tercantum dalam fatwa DSN-MUI No.10/DSN-MUI/VI/2000.